2016
DOI: 10.1002/anie.201610251
|View full text |Cite
|
Sign up to set email alerts
|

Knight Shift in 13C NMR Resonances Confirms the Coordination of N‐Heterocyclic Carbene Ligands to Water‐Soluble Palladium Nanoparticles

Abstract: The coordination of N-heterocyclic carbene (NHC) ligands to the surface of 3.7 nm palladium nanoparticles (PdNPs) can be unambiguously established by observation of Knight shift (KS) in the C resonance of the carbenic carbon. In order to validate this coordination, PdNPs with sizes ranging from 1.3 to 4.8 nm were prepared by thermal decomposition or reduction with CO of a dimethyl NHC Pd complex. NMR studies after CO adsorption established that the KS shifts the C resonances of the chemisorbed molecules severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…The crystallite size calculated from the XRD data using the Scherrer equation (2.2 nm) was much smaller than the mean size obtained by TEM. A similar divergence between TEM and XRD radii was found in PdNPs 2 a , and was ascribed to the polycrystallinity of the nanoparticles observed in the HR‐TEM images (Figure b)…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The crystallite size calculated from the XRD data using the Scherrer equation (2.2 nm) was much smaller than the mean size obtained by TEM. A similar divergence between TEM and XRD radii was found in PdNPs 2 a , and was ascribed to the polycrystallinity of the nanoparticles observed in the HR‐TEM images (Figure b)…”
Section: Resultssupporting
confidence: 72%
“…Concerning PdNPs, Glorius and co‐workers have reported the preparation of water‐stable Pd nanoparticles stabilized by charged NHC ligands . In a recent work, we have also communicated the synthesis and characterization of water‐soluble NHC‐stabilized PdNPs prepared by decomposition of a dimethyl NHC metal complex . The coordination of the NHC ligand to the metal surface of these nanoparticles was confirmed by the observation of a Knight‐shifted signal for the carbenic carbon in solid state 13 C NMR spectra.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…We have recently shown that the thermal decomposition of [Pd(NHC) 2 Me 2 ] complexes produces Pd nanoparticles that are solubilized and stabilized in water by sulfonated NHC ligands coordinated to their surface (Scheme 6). 8 These nanoparticles (mean diameter of 3.8 ± 0.8 nm) are reminiscent of the type of Pd aggregates that might form in the above catalytic solutions. Our guess was supported by the observation that these nanoparticles were also able to afford full conversions in the oxidation of 1-phenylethanol under the same conditions that complex 4 S , indicating that they are at least as active as this complex in this reaction(Scheme 6).…”
Section: Scheme 4 Catalytic Oxidation Of 1-phenylethanolmentioning
confidence: 99%
“…5 We are interested in the synthesis, reactivity, and applications of transition-metal complexes with water-soluble NHC ligands. 6,7,8 Herein, we report the synthesis and characterization of new palladium complexes with Nheterocyclic chelate ligands functionalized with sulfonate, carboxylate or ammonium groups. An account of the aqueousphase reactivity of these complexes, and their behavior as catalysts in the aerobic oxidation of alcohols 9,10 in water, is reported.…”
Section: Introductionmentioning
confidence: 99%